Purification effects of recycled aggregates from construction waste as constructed wetland filler. (December 2022) - Li, Yajiao; Wang, Jiaping; Lin, Xingchen; Wang, Hui; Li, Huaien; Li, Jiake
Abstract: Three groups of constructed wetlands based on gravel (#1), asphalt concrete + red brick (#2), and red brick (#3) were constructed to explore their purification effects and the characteristics of microbial community structure. The results show that the construction waste recycled aggregates have little leaching risk of heavy metals; the adsorption of nitrogen and phosphorus by the three fillers could be well fitted by pseudo-first-order and pseudo-second-order kinetic models (R 2 > 0.96); the adsorption of NH4 + -N by the three fillers could be well fitted by the Freundlich model (R 2 > 0.656); the adsorption of phosphorus could be well fitted by the Langmuir and Freundlich models, except for gravel (R 2 > 0.875). The average removal rate of COD, NH4 + -N, TN, and TP was 60.85 %, 94.69 %, 73.42 %, 39.12 % (#1); 67.32 %, 20.31 %, 22.26 %, 27.81 % (#2); 67.35 %, 17.7 %, 25.8 % and 46.98 % (#3). There was no significant difference in the purification effect of the three fillers on COD. The adsorption effect on NH4 + -N was: gravel > red brick/asphalt concrete, and the adsorption effect on TP was: asphalt concrete > red brick > gravel. The microbial population richness of the upper filler was #2 > #1 > #3, the uniformity was #1 > #2 > #3, and the diversity was #1/#2 > #3. The microbial communities were dominated by Proteobacteria, Actinobacteriota, Bacteroidota and Chloroflexi . Graphical abstract: Unlabelled Image Highlights: The safety of different construction waste recycled aggregates was clarified. The adsorption mechanism of construction waste recycled aggregates was explained. The effects of construction waste recycled aggregates on tail water were studied. The microbial community structure on the surface of different fillers was determined.